Optimization of glycerol fermentation conditions for bioethanol production by locally isolated Escherichia coli SS1 - Suhaimi, Sheril Norliana (2013)
The increase of biodiesel production worldwide lead to the increase of glycerol present in environment. Bioconverting glycerol into various valuable products is one of glycerol’s promising applications due to its high availability,lower costs and existence of many glycerol-utilizing microorganisms. Bioethanol is one of the interest products generated and its production is depending on the types of microorganism used and fermentation conditions. The effective screening procedure is needed to screen and isolate broad ranges of bacteria from environment. This study aims to isolate a suitable glycerol-fermenting microorganism and able to produce high ethanol production under optimized condition using crude glycerol as a substrate. The screening method was modified based on enzymatic oxidation of ethanol which is correlated to reduction of 2,6-dichlorophenol-indophenol dye. The formation of decolourized zone was apparent using modified assay containing 5 ml/L of 0.05 M 2,6-dichlorophenol-indophenol, 10 ml of reaction mixture and 500 μl/L of enzyme, respectively. In this study, several isolates were obtained showing capability in producing ethanol. The isolate namely E.coli SS1 was obtained after several screening processes. The fermentation of glycerol was carried out in batch fermentation using 120 mL serum bottle, incubated in 37°C with 120 rpm of agitation under anaerobic condition. The maximum ethanol production was achieved at 96 hours with 9.23 g/L, which is corresponding to the yield of 1 mol ethanol per mol glycerol and the productivity of 0.01 mol/molh-1. This isolate also showed a higher affinity to glycerol than glucose for bioethanol production. Response surface methodology (RSM) employed to obtain optimized condition. Six parameters were subjected to two level factorial design which were initial pH, substrate concentration, sodium chloride content, trace element solution, incubation temperature and the concentration of yeast extract and tryptone. The results showed that only 4 parameters were identified as significant factors, i.e initial pH, substrate concentration, sodium chloride content and the mixture of yeast extract and tryptone. The effect of the significant variables was subsequently evaluated in Central Composite Design (CCD) to determine the optimum value for each variable. The optimized conditions obtained were at initial pH of 7.61, substrate concentration of 34.5 g/L, the mixture of yeast extract and tryptone at 6.42 g/L whereas salt content was identified as a non-significant parameter, with predicted maximum ethanol production of 17.05 g/L (1.0 mol/mol). Avalidation run was performed using crude glycerol based on optimized conditions and maximum ethanol obtained was 15.72 ± 0.26 g/L with the yield of 1.0 mol/mol and productivity at 0.01 mol/mol.h-1 which was comparable to the predicted ethanol concentration. The isolated E.coli SS1 is a potential ethanol producer from glycerol, where the increased ethanol production is observed under optimized fermentation conditions. The crude glycerol also is feasible to be fermented using this isolate for comparable ethanol production using pure glycerol.